A control structure for a bidirectional dc-ac converter with power quality support functions - Ribeiro, Laila Sindra (2022)
The expansion of distributed generation, especially photovoltaic, provokes an increase in the number of DC-AC converters connected to the grid. These converters may offer power grid support functions such as power factor correction and compensation of the current harmonic components. Those functions raise the equipment relevance to the grid and contribute to the power system’s confiability and power quality. In this context, the objective of this work is to design a DC-AC converter with the grid support functions as power factor correction and harmonic compensation, besides electrical power interchange. The work focuses on the controller of the converter, with the algorithms embedded in a DSP and power converter in a Hardware In the Loop (HIL). This dissertation includes a theoretical background of the converter topology operation, filter design, and control loops used in the project. Experimental results demonstrate that the converter is capable of operating with grid support functions with a good performance, correcting power factor and compensating 3rd, 5th, and 7th harmonics. Furthermore, the converter can have multiple functions activated, distributing its power capacity to prioritize the chosen operation mode.